Passagens por territórios do YouTube: sentidos identitários de América Latina na plataforma e imagens da tecnocultura contemporânea - Orlandin, Jardel (Universidade do Vale do Rio dos Sinos, 2020)
The objective of this research is to study the production of identity meanings in technical images on YouTube. Therefore, we opted to search for Latin America, following trails established by the website and creating new ways of exploring the less visible territories. Inspired by the perception of Latinity identity meanings present in the most viewed video on YouTube so far, Despacito (LUIS FONSI, 2017a), we unveil the methods by which the website operates and builds its territories of experience and meaning. Ethicities, frames and imaginaries (KILPP, 2003) are basic concepts for this research, which starts off from the technocultural perspective (FISCHER, 2013; McLUHAN, 2007; FLUSSER, 2013; BENJAMIN, 2012). Other concepts contribute so that we are able to map YouTube’s technical qualities and understand its ways of producing identity meanings. We also work with algorithms (PARISER, 2012), with montages (EISENSTEIN, 2002; MANOVICH, 2005) and with the audiovisual on the web (MONTAÑO, 2015). As a methodological proposal, we conceived an analysis itinerary for the media and the messages. Illuminated by the figure of the flâneur, we roamed through the website and found four main passages (BENJAMIN, 2009) – which we understand as dense, complex territories, that recover different imaginaries and tension a series of boundaries that have been hitherto consolidated. We identified as passages: 1) the home page – a safe space for the user and infinite video storehouse; 2) the search bar – facilitating and friendly, a transportation to new spaces; 3) the scattered channels and pages – which constantly suggest new links to the users; and 4) the list of most viewed videos – which reinforces the number of accesses or clicks as a way of acting on the platform. In each territory, we consider several elements of YouTube, from the content to the interface and the algorithms. We perceive the presence, albeit with tension, of other audiovisual media, such as cinema and television. The media constructs that we see, of Brazil, Mexico and Latin America, are passages for YouTube itself and its worlds, programmed by algorithms, interfaces, settings, links etc. As these same passages are present on countless other platforms, shaping our perception, they are also images of the contemporary technoculture.
Keywords: Sentidos identitários; Tecnocultura audiovisual; YouTube; Montagens; Interface; Identity meanings; Audiovisual technoculture; Montage; ACCNPQ::Ciências Sociais Aplicadas::Comunicação